Effect of Epistemological Belief on Teaching Efficacy: A Survey of Gandaki Province of Nepal - Chhetri, Deb Bahadur; Joshi, Dirgha Raj (Janabhawana Research Journal, 2025)
The research aimed to identify the status of mathematics teachers' epistemological beliefs and teaching efficacy, as well as the effect of epistemological beliefs on teaching efficacy. This cross-sectional survey was conducted among 267 secondary-level mathematics teachers working in community schools in Gandaki Province, Nepal. The major statistical techniques employed in the research were the t-test, one-way ANOVA, and hierarchical multiple regression to analyze the data. The findings indicated that the level of mathematics teachers in epistemological beliefs and teaching efficacy, as well as age, academic background, qualification, and experience, plays a significant role in shaping epistemological beliefs and teaching efficacy, which is found to be significantly high. The results further show that epistemological belief significantly predicts teaching efficacy.